2004
DOI: 10.1002/tea.20007
|View full text |Cite
|
Sign up to set email alerts
|

In search of pedagogical content knowledge in science: Developing ways of articulating and documenting professional practice

Abstract: This study examines the development of ways of documenting and portraying science teachers' pedagogical content knowledge (PCK). As a result of a longitudinal study into science teachers' pedagogical content knowledge, a method is developed for capturing and portraying PCK that comprises two important elements. The first is linked to the particular science content, termed Content Representation (CoRe), and the second is linked to teaching practice, termed Professional and Pedagogical experience Repertoire (PaP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
325
0
106

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 531 publications
(436 citation statements)
references
References 22 publications
5
325
0
106
Order By: Relevance
“…PST F, a mature aged PST, observed that their previous experience in industry was important "so can relate real world experience to the students". Loughran, Mulhall, and Berry (2004) found that when teachers talk about PCK, they describe their practice and how it is related to content understanding. PST M indicated that in the past they had looked at teaching from a "traditional teaching sense -proven strategies, classic learning styles … but TPACK highlights the importance of the third element (technology)."…”
Section: Perceptions Of the Elements Of Tpackmentioning
confidence: 99%
“…PST F, a mature aged PST, observed that their previous experience in industry was important "so can relate real world experience to the students". Loughran, Mulhall, and Berry (2004) found that when teachers talk about PCK, they describe their practice and how it is related to content understanding. PST M indicated that in the past they had looked at teaching from a "traditional teaching sense -proven strategies, classic learning styles … but TPACK highlights the importance of the third element (technology)."…”
Section: Perceptions Of the Elements Of Tpackmentioning
confidence: 99%
“…However, few practice-based assessments are designed to measure the professional knowledge that science teachers are called on to use as they engage in these tasks of teaching. The practice-based CKT assessments that measure the knowledge used in teaching science focus mainly on science teachers' pedagogical content knowledge (Lee, Brown, Luft, & Roehrig, 2007) and involve teachers in tasks that require substantial time to administer and score, such as analyzing video-recorded episodes of practice (Roth et al, 2011), participating in think-aloud or cognitive interviews (Henze & van Driel, 2015;Park & Suh, 2015), conducting classroom observations (Park & Oliver, 2008;Park & Suh, 2015), or documenting their pedagogical content knowledge for particular science topics using graphic organizers (Bertram & Loughran, 2012;Loughran, Mulhall, & Berry, 2004). To date, only a few notable efforts have developed large-scale, practice-based assessment items to measure the professional knowledge specialized to science teaching (Sadler, Sonnert, Coyle, Cook-Smith, & Miller, 2013;Smith & Taylor, 2010).…”
Section: Assessing Content Knowledge For Teaching Sciencementioning
confidence: 99%
“…Several authors (Loughran, Mulhall & Berry, 2004;Magnusson, Krajcik & Borko, 1999;Park & Chen, 2012;Van Driel, Verloop &de Vos, 1998 andVeal &MaKinster, 1999) have noted the topic-specific nature of PCK. More recently, Mavhunga and Rollnick (2013) defined and described Topic-Specific PCK (TSPCK) as the capacity to transform the subject matter of a given topic for the purpose of teaching.…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%
“…The latter lead to the identification of Big Ideas for teaching particular topics, while PaPeRs are narrative accounts of practice designed to bring to life the ideas in the CoRe. The Big Ideas highlight a number of key concepts commonly viewed by practitioners as important for students to learn in order to understand the topic (Loughran et al, 2004). Whilst models of PCK and tools such as CoRes and PaP-eRS allow researchers to identify PCK in their research data, the process is timeconsuming as most of the research is based on case studies.…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%